Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.308
|View full text |Cite
|
Sign up to set email alerts
|

The Making of a 'Top' Open Data City: A Case Study of Edmonton’s Open Data Initiative

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Stakeholder analysis and perspectives analysis show that add value to OGD by exposing the identity, power, motivations, and worldview of key actors [11]. They provide a necessary foundation of knowledge for both researchers and practitioners who need to understand the different meanings of OGD in any particular context [11].Despite the impact and benefits of the usability, previous research has demonstrated that a great deal of emphasis is placed on the availability of datasets over other aspects of these initiatives [12]. This may de-emphasize work to enhance the navigation and usability of the system itself.…”
Section: The Value Of Ogdmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholder analysis and perspectives analysis show that add value to OGD by exposing the identity, power, motivations, and worldview of key actors [11]. They provide a necessary foundation of knowledge for both researchers and practitioners who need to understand the different meanings of OGD in any particular context [11].Despite the impact and benefits of the usability, previous research has demonstrated that a great deal of emphasis is placed on the availability of datasets over other aspects of these initiatives [12]. This may de-emphasize work to enhance the navigation and usability of the system itself.…”
Section: The Value Of Ogdmentioning
confidence: 99%
“…Others have found that OGD portals situate the government as a data custodian rather than a service provider [13,14]. Although studies have examined policies [13,15], data sources [12,16], theoretical research on data publics [17], efforts to promote OGD portals on social media [18], and the use of these tools by technology-savvy users [19], we found that there is very limited research related to the feedback on the performance of open data portals and the use of this data from user's perspective as they engage in local decision-making processes.…”
Section: The Value Of Ogdmentioning
confidence: 99%
“…To this end, PSOs could use the ideas and knowledge of contributors through coproduction activities facilitated, for instance, by innovation competitions such as hackathons, cooperathon or startup weekends. PSOs could also foster the self-provision of services by citizens through the installation of appropriate infrastructures, such as community portals for collaborative decision-making [10] and through effective incentives [35].…”
Section: Open Innovation In the Public Sectormentioning
confidence: 99%